EFFORTS TO IMPROVE MATHEMATICS LEARNING ACTIVITIES USING COOPERATIVE LEARNING MODELS NUMBERED HEAD TOGETHER (NHT) TYPE IN CLASS VII SMP - Rika Susanti; Romelan Hamzah (Universitas Ahmad Dahlan, 2019)
Learning mathematics is still a lesson that is considered difficult for students. Student activities also seemed to be still low in class VII-D in the even semester of SMP Negeri 1 Imogiri. Bantul Regency. This study aims to improve mathematics learning activities using the Numbered Head Together (NHT) type of cooperative learning model for seventh-grade students in the even semester of the SMP Negeri 1 Imogiri in Bantul Regency 2018/2019 academic year. This research was included in the classroom action research consisting of two cycles. This study's settings were students of class VII-D State Junior High School (SMP Negeri) 1 Imogiri Bantul Regency 2018/2019 academic year. Data collection in this study uses observation methods and interview guidelines. The instruments in this study used observation sheets and interviews. The data analysis technique in this study used a qualitative descriptive method. The results showed that the Numbered Head Together type of cooperative learning model could improve students' mathematics learning activities in class VII-D SMP Negeri 1 Imogiri Â Bantul Regency 2018/2019 academic year. This is evident from the results of observations of mathematics learning activities of students who experienced an increase in each cycle and a positive response from the results of teacher and student interviews. In the first cycle, the percentage of students' mathematics learning activities was 60.75%, and in the second cycle, the average percentage of observations of student activities increased by 75.47%. The results of interviews obtained information that, in general, students are interested and feel happy in learning mathematics using the cooperative learning model Numbered Head Together.